Optimal allocation of capacitors in radial distribution systems with distributed generation - Franco, John F. [UNESP]; Rider, Marcos J. [UNESP]; Lavorato, Marina [UNESP]; Romero, Rubén [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper presents a mixed-integer linear programming approach to solving the optimal fixed/switched capacitors allocation (OCA) problem in radial distribution systems with distributed generation. The use of a mixed-integer linear formulation guarantees convergence to optimality using existing optimization software. The results of one test system and one real distribution system are presented in order to show the accuracy as well as the efficiency of the proposed solution technique. © 2011 IEEE.
Keywords: AMPL; CPLEX; Distribution system optimization; mixed-integer linear programming; optimal allocation of capacitors; Distribution systems; Mixed integer linear programming; Optimal allocation; Capacitors; Distributed power generation; Innovation; Integer programming; Linear programming; Local area networks; Optimization; Smart power grids; Distributed computer systems